Indian Stock Market Reaction to the Quarterly Earnings Information - Iqbal; Mallikarjunappa, T. (Indian Journal of Finance, 2009)
This paper examines stock market reaction to the earnings announcements by taking December 2001 quarter earnings announcement as an event. The study is based on 152 companies having minimum 20 percent foreign holdings. The companies are divided into, good news, bad news and overall portfolios. We have used event study methodology, t test, Runs test, sign test, raw returns and log returns. The behaviour of AARs and CAARs are examined for 30 days before and 31 days after the announcement of quarterly earnings. The results of the study revealed that stock market reaction to the earnings announcements is delayed.